Regression of gastric T cell lymphoma with eradication ofHelicobacter pylori. Issue 2 (1st February 2001) - Bariol, C; Field, A; Vickers, C R; Ward, R
Abstract : Helicobacter pylori is thought to be important in the pathogenesis of chronic active gastritis, peptic ulceration, gastric adenocarcinoma, and gastric B cell lymphoma of mucosa associated lymphoid tissue. The mechanism of evolution from chronic gastritis to monoclonal B cell proliferation is not known but is thought to be dependent on antigen specific T cells to H pylori and its products. Here, we report a case of gastric T cell lymphoma associated with chronic H pylori gastritis which regressed with eradication of the organism. This is the first report of a gastric T cell lymphoma regressing with H pylori eradication, and suggests a causal link between primary gastric T cell lymphoma and this organism.